Inhibitors of Nucleotide Biosynthesis as Candidates for a Wide Spectrum of Antiviral Chemotherapy - Sepúlveda, Claudia Soledad (2022)
Emerging and re-emerging viruses have been a challenge in public health in recent decades. Host-targeted antivirals (HTA) directed at cellular molecules or pathways involved in virus multiplication represent an interesting strategy to combat viruses presently lacking effective chemotherapy. HTA could provide a wide range of agents with inhibitory activity against current and future viruses that share similar host requirements and reduce the possible selection of antiviral-resistant variants. Nucleotide metabolism is one of the more exploited host metabolic pathways as a potential antiviral target for several human viruses. This review focuses on the antiviral properties of the inhibitors of pyrimidine and purine nucleotide biosynthesis, with an emphasis on the rate-limiting enzymes dihydroorotate dehydrogenase (DHODH) and inosine monophosphate dehydrogenase (IMPDH) for which there are old and new drugs active against a broad spectrum of pathogenic viruses.